Phytochemical screening and molluscicidal activity of Excoecaria agallocha bark extracts. - Olano, Dave Eldon Bance
One of the persistent problems of the country's agricultural sector is Golden Apple Snail (GAS) infestation. As a result of efforts to control this pest, petroleum-based molluscicides have been in high demand. But, due to its detrimental effects, there is an increased attention for the use of plant molluscicides as an alternative., E. agallocha bark was extracted with 80 percent MeOH and further subjected to serial liquid- liquid extraction with n-Hexane, DCM and EtOAC. It was concentrated at reduced prerssure and 40 degrees centigrade and biassayed in a negative control (tapwater), positive control (4ppm Niclosamide Bayluscide); and 100, 150, 300, and 600 ppm solvent fractions for 48 hours. The LC50 of MeOH, n-Hexane, DCM, EtOAc and Aqueous fractions were 77.13, 124.88, 159.14, 372.73, and 560.75 ppm respectively, with the following increasing molluscocodal activity: Aq<EtOAc<DCM<n-Hexane<MeOH. The MeOH extract was determined to be the most effective molluscicidal agent because 100 percent mortality occurred six to 12 hours earlier than other extracts and it required the least concentration for LC50. Furthermore, phytochemical screening detected presence of alkaloids, tannins, saponins and terpenoids in the solvent fraction.